Charge-transfer and isomerization reactions of trans-4-(N-arylamino)stilbenes. Issue 40 (3rd October 2016) - Yao, Hsuan-Hsiao; Cheng, Hsu-Hsiang; Cheng, Chao-Han; Lin, Cheng-Kai; Yang, Jye-Shane; Chen, I-Chia
Abstract : Competition of charge-transfer and isomerization reactions of trans -4-( N -arylamino)stilbenes. Abstract : We studied the excited-state dynamics of trans -4-( N -arylamino)stilbenes with aryl = phenyl (p1H), 4-methoxyphenyl (p1OM), or 4-cyanophenyl (p1CN) in solvents of varied polarity and viscosity by using femtosecond transient absorption and time-correlated single photon counting techniques. In nonpolar solvents the decay is triexponential, in which the rapid component corresponds to vibrational cooling combined with solvation, the intermediate temporal component 41–120 ps to trans – cis isomerization, and the long one ∼1 ns to fluorescence decay of the S1 state. The S1 state has a delocalized geometry and charge-transfer characteristics, corresponding to a planar intramolecular charge transfer (PICT) state. In polar solvents, an excited-state absorption band appears near 520 and 480 nm for p1OM and p1CN, respectively but not for p1H. This band has a rise lifetime of 4.3/7.5, 16.3/9.4, and 29.5/16 ps for p1CN/p1OM in acetonitrile (ACN), dimethylformamide (DMF), and dimethyl sulfoxide (DMSO), respectively and matches the decay of the 600 nm PICT band. This band is thus assigned to the absorption of a singlet twisted intramolecular charge transfer state (TICT). The conversion rate decreases as the solvent viscosity is increased and is consistent with a large structural variation amplitude. Theoretical calculations using density functional theory (DFT), method PEB0, were employed to obtain the optimized structures and energies of those states. The PICT state possesses delocalized π electrons along the molecule. The TICT for p1CN is formed by twisting about the aminostilbene–benzonitrile C–N bond by ∼90°, but it is about the stilbene–aniline C–N bond for p1OM. We observed faster conversion rates for p1CN in alcoholic solvents, in which the lifetimes for both the PICT and TICT states are shortened to 20–99 ps and 120–660 ps, respectively, as a result of solvent–solute H-bonding interactions. In p1OM, the TICT state has an elongated CC bond in the stilbene moiety, which might facilitate the trans – cis isomerization reaction and thus account for the relatively short lifetime of 58–420 ps in polar solvents.